Health and Artificial Intelligence in the context of COVID-19 and beyond - Navas Navarro, Susana (2021)
This article introduces the main relevant aspects of ehealth or “digital health.” In this regard, by way of an introduction, the concept of health is addressed. In the second section, the core of this article, different aspects regarding the relationship between health and technology (HealthTech) are highlighted. Next, the importance of technology in order to deliver a preventive and personalized medicine, tailor-made to each patient, is addressed. Then, in the fourth section, some discriminatory situations that may arise due to not being able to access technology are discussed. Finally, I make some remarks regarding the so-called “Internet of Bodies".